Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/ejh.12977
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled study evaluating effects of amlodipine addition to chelators to reduce iron loading in patients with thalassemia major

Abstract: Addition of amlodipine to iron chelators has beneficial effects for reduction of iron loading in patients with thalassemia major. This combination therapy seems safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 15 publications
5
29
0
Order By: Relevance
“…A limited number of human studies have shown a significant reduction in MIC after using amlodipine 2628. Hence, we conducted a randomized, controlled-placebo study to demonstrate the efficacy of amlodipine, in addition to chelation therapy, in reducing myocardial iron concentration.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of human studies have shown a significant reduction in MIC after using amlodipine 2628. Hence, we conducted a randomized, controlled-placebo study to demonstrate the efficacy of amlodipine, in addition to chelation therapy, in reducing myocardial iron concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Despite incomplete characterization of iron-induced K + current alterations, amiodarone has been used to treat supraventricular arrhythmias commonly found in iron-overload patients ( Pennell et al, 2013 ). Potential role of LTCC blockers as an inhibitor of cardiac iron uptake is also being evaluated in clinical trials ( Fernandes et al, 2013 , 2016 ; Shakoor et al, 2014 ; Eghbali et al, 2017 ; Sadaf et al, 2018 ). It is still unknown whether the use of LTCC blockers will exert any significant electrophysiological effects.…”
Section: Forging the Field: Additional Issues To Be Explored In Iron-mentioning
confidence: 99%
“…Iron overload is an important cause of mortality and morbidity in chronic transfusion-dependent states commonly exemplified by transfusion-dependent beta-thalassaemia syndromes [including non-transfusion-dependent (NTD) thalassaemia intermedia] as well as transfusion-dependent myelodysplastic syndromes (MDS). Hence, therapeutic iron chelation is indicated in these conditions12345. There seems to be an increasing interest for different iron chelators and labile iron pool for patients with thalassaemia syndromes (thalassaemia major and thalassaemia intermedia) and transfusion-dependent MDS with respect to their efficacy, tolerability, safety, cost and long-term side effects.…”
mentioning
confidence: 99%
“…There seems to be an increasing interest for different iron chelators and labile iron pool for patients with thalassaemia syndromes (thalassaemia major and thalassaemia intermedia) and transfusion-dependent MDS with respect to their efficacy, tolerability, safety, cost and long-term side effects. Several studies have been published recently on this topic123456789. Di Maggio and Maggio4 evaluated 10 trials on various iron chelators singly or in combination for iron overloaded transfusion-dependent beta-thalassaemia major.…”
mentioning
confidence: 99%
See 1 more Smart Citation